2016
DOI: 10.1093/annonc/mdw201.40
|View full text |Cite
|
Sign up to set email alerts
|

RM-043 Eruptive seborrheic keratosis (ESK) and its association with gastrointestinal cancer (GIC): a case-control study and meta-analysis

Abstract: Conclusion:In Colombian patients, seborrheic keratosis and eruptive seborrheic keratosis of less than 6 months onset is highly suggestive of an association with gastrointestinal cancer. Additional studies are required to confirm this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Given the small sample size, no conclusions could be made on the association between ESK and malignancy. 16 - 18 Another criticism of ESK’s link to malignancy is that the incidence of both seborrheic keratoses and cancer is higher in older patients. 24 While the majority of patients were elderly in our analysis, we found that 31.4% ( n = 22/70) of patients who had ESK prior to a cancer diagnosis were under the age of 60.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the small sample size, no conclusions could be made on the association between ESK and malignancy. 16 - 18 Another criticism of ESK’s link to malignancy is that the incidence of both seborrheic keratoses and cancer is higher in older patients. 24 While the majority of patients were elderly in our analysis, we found that 31.4% ( n = 22/70) of patients who had ESK prior to a cancer diagnosis were under the age of 60.…”
Section: Discussionmentioning
confidence: 99%
“…Given the low incidence rate, an association between ESK and malignancy could not be made. [16][17][18]…”
Section: Malignant Conditionsmentioning
confidence: 99%